Formulation and Evaluation of Phytosomes Loaded with Pithecellobium Bijeninum Leaf Extract - Arihant Jain; Richa Verma; Parulben D Mehta (Current Research in Pharmaceutical Sciences, 2023)
The objective of the present study was to prepare phytosomal formulation loaded with aqueous extract of Pithecellobium bijeninum leaves. The extraction of leaf powder was done by maceration technique using 90:10 ethanol-water mixture with an extraction yield of 6.12%. The extract was found to contain alkaloids, and flavonoids and the total phenolic content was found to be 23.2 ± 0.827 %w/w. Phytosomes of the extract were prepared by solvent evaporation method using lecithin as the lipid molecule. The particle size of the phytosomes was from 468 nm to 1827 nm in size with a polydispersity index varying between 0.178 - 0.464. The phytosomes were visible as rigid, almost spherical vesicles in SEM image. The surface of the phytosome vesicles was found to be regular and smooth. The point prediction suggested level 3 (0.3 g) of lipid concentration and level 2 (0.2 g) of extract concentration to present the lowest particle size. Sharp and distinct endothermic peaks in DSC revealed the formulation of stable phytosomes due to molecular interactions between the extract and lecithin. The phytosomes were found to possess good antioxidant action against DPPH radical in the in vitro scavenging assay. The IC50 value of the extract against DPPH was found to be 48.24 µg and that of the phytosomal formulation loaded with the extract (F4) was obtained to be 48.90 µg.